Proceedings of 20th Biennial Conference on Precision Electromagnetic Measurements
DOI: 10.1109/cpem.1996.547347
|View full text |Cite
|
Sign up to set email alerts
|

A new solution of high precision wideband time-division wattmeter

Abstract: A new solution of the time &vision multiplier of the Goldberg type applied in the high precision wattmeter is presented. The solution is based on the method of compensating the systematic frequency error leading thus to the hgh performances of the multiplier even in the case when the conversion frequency is only 10 times the frequency of the signals to be measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This new method is based on two identical multipliers which works on two different frequencies. All advantages mentioned above about method [7] are also valid for the method based on two multipliers which is presented in this paper. There are some other additional advantages of this method comparing to the method [7] related to the practical realization which will be described in the paper.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…This new method is based on two identical multipliers which works on two different frequencies. All advantages mentioned above about method [7] are also valid for the method based on two multipliers which is presented in this paper. There are some other additional advantages of this method comparing to the method [7] related to the practical realization which will be described in the paper.…”
Section: Introductionmentioning
confidence: 77%
“…It has been shown that for practical realization of the method there is no need to duplicate all functional of the two TDMs, but some simplifications are possible. Unlike the compensation method [7] this method enables possibility to couple secondary coil of the current transformer directly to analog multiplexer of the pulse amplitude modulating circuit as in [2]. A watt converter based on this method has been developed and results of measurements show that at the unity power factor precision of +/-50x10".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation